Hidden in Plain View: Discovery of Chimeric Diabetogenic CD4 T Cell Neo-Epitopes - Reed, Brendan K.; Kappler, John W. (Frontiers in Immunology, 2021)
The T cell antigens driving autoimmune Type 1 Diabetes (T1D) have been pursued for more than three decades. When diabetogenic CD4 T cell clones and their relevant MHCII antigen presenting alleles were first identified in rodents and humans, the path to discovering the peptide epitopes within pancreatic beta cell proteins seemed straight-forward. However, as experimental results accumulated, definitive data were often absent or controversial. Work within the last decade has helped to clear up some of the controversy by demonstrating that a number of the important MHCII presented epitopes are not encoded in the natural beta cell proteins, but in fact are fusions between peptide fragments derived from the same or different proteins. Recently, the mechanism for generating these MHCII diabetogenic chimeric epitopes has been attributed to a form of reverse proteolysis, called transpeptidation, a process that has been well-documented in the production of MHCI presented epitopes. In this mini-review we summarize these data and their implications for T1D and other autoimmune responses.